2019
DOI: 10.3389/fncel.2019.00341
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Ensheathing Cells Grafted Into the Retina of RCS Rats Suppress Inflammation by Down-Regulating the JAK/STAT Pathway

Abstract: The inflammatory microenvironment in the retina plays a vital role in the pathogenesis and progression of retinitis pigmentosa (RP). Microglial inflammatory cytokines production leads to gliosis and apoptosis of retinal neurons, and ultimately, visual loss. Cell-based therapies using grafted olfactory ensheathing cells (OECs) have demonstrated modulation of degenerative microenvironments in the central nervous system (CNS), in a number of animal models. However, mechanisms by which grafted OECs can reduce dege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 66 publications
0
22
0
Order By: Relevance
“…In vitro, oxalate caused a dose-dependent increase in the secretion of inflammatory factors, including MDA, IL-6, TNF-α, and CRP, in HAECs but not in HASMCs, indicating that vascular endothelial cells might be the target cells of oxalateinduced vascular calcification. The JAK2/STAT3 signaling pathway plays an important role in regulating the secretion of inflammatory factors [34,35]. Our study indicated a potential role for JAK2/STAT3 signaling in increasing the inflammatory factors and activating oxidative stress by high oxalate concentrations as p-JAK2 and p-STAT3 levels were significantly upregulated in HAECs.…”
Section: Discussionmentioning
confidence: 62%
“…In vitro, oxalate caused a dose-dependent increase in the secretion of inflammatory factors, including MDA, IL-6, TNF-α, and CRP, in HAECs but not in HASMCs, indicating that vascular endothelial cells might be the target cells of oxalateinduced vascular calcification. The JAK2/STAT3 signaling pathway plays an important role in regulating the secretion of inflammatory factors [34,35]. Our study indicated a potential role for JAK2/STAT3 signaling in increasing the inflammatory factors and activating oxidative stress by high oxalate concentrations as p-JAK2 and p-STAT3 levels were significantly upregulated in HAECs.…”
Section: Discussionmentioning
confidence: 62%
“…In vitro microglial activation was induced by LPS (Figure 7 A). Highly aggressive proliferating immortalized (HAPI) microglial cells were treated with LPS (1 mg/mL) for 4 h 28 before co-culturing with OECs or IL-1Ra knockdown OECs in the transwell co-culture system for another 24 h. The results obtained from immunocytochemistry indicated that the LPS stimulation significantly activated HAPI microglial cells (Figure 7 B). The averaged fluorescent intensity of microglial markers Iba-1 and CD40 was significantly increased (64.52 ± 1.37 vs. 39.48 ± 0.82, p < 0.0001 and 60.67 ± 3.85 vs. 48.48 ± 0.71, p < 0.0001, respectively).…”
Section: Resultsmentioning
confidence: 97%
“…Neuroinflammation is considered as a predominant pathological hallmark of brain damage after SAH [ 32 , 33 ]. During neuroinflammation following SAH, activated microglia are a pivotal source for a plethora of various cytokines and chemokines in the central nervous system [ 34 ].…”
Section: Discussionmentioning
confidence: 99%